2015
DOI: 10.1155/2015/704982
|View full text |Cite
|
Sign up to set email alerts
|

Nephrogenic Adenoma of the Urinary Bladder: A Review of the Literature

Abstract: Background. Nephrogenic adenoma of the urinary bladder (NAUB) is a rare lesion associated with nonspecific symptoms and could inadvertently be misdiagnosed. Aim. To review the literature. Methods. Various internet search engines were used. Results. NAUB is a benign tubular and papillary lesion of the bladder, is more common in men and adults, and has been associated with chronic inflammation/irritation, previous bladder surgery, diverticula, renal transplantation, and intravesical BCG; recurrences and malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 64 publications
0
35
0
Order By: Relevance
“…As nephrogenic adenomas are rare lesions, they can easily be confused and/or misdiagnosed as a variety of other malignant lesions of the urinary system. These can be associated with various inflammatory processes, to include: recurrent urinary tract infections, urinary calculi, prior renal transplants, bladder wall diverticulum, radiotherapy as well as chemical agents and other irritative therapies [5 , 7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As nephrogenic adenomas are rare lesions, they can easily be confused and/or misdiagnosed as a variety of other malignant lesions of the urinary system. These can be associated with various inflammatory processes, to include: recurrent urinary tract infections, urinary calculi, prior renal transplants, bladder wall diverticulum, radiotherapy as well as chemical agents and other irritative therapies [5 , 7] .…”
Section: Discussionmentioning
confidence: 99%
“…Nephrogenic adenomas primarily occur in adults, with males 3 times more likely to have NA than women [4] . Ten percent of nephrogenic adenomas occur in children [5] . Reported cases of nephrogenic adenomas in children exclusively involve the bladder with the most frequent predisposing factor being reimplantation of the ureters for vesicoureteral reflux [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed recurrence in five patients and Gordetsky's recent study found one in 31 patients with recurrence. Other studies had varying numbers of recurrence, but recommendations were made to have long term follow-up as recurrences were common ( 5 – 8 , 13 , 14 , 20 ). Given the symptomatic nature of this lesion and its tendency to recur, it would be prudent to follow patients with a cystoscopy and treat any of these recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up studies have indicated that nephrogenic adenomas in the genitourinary tract can recur after resection but do not progress to carcinoma or metastasize. 4 Two case reports have described bladder tumors that appear to have undergone malignant transformation from nephrogenic adenoma to adenocarcinoma, underscoring the importance of continued follow-up for patients with nephrogenic adenoma. 4 …”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“… 4 Two case reports have described bladder tumors that appear to have undergone malignant transformation from nephrogenic adenoma to adenocarcinoma, underscoring the importance of continued follow-up for patients with nephrogenic adenoma. 4 …”
Section: Discussion and Literature Reviewmentioning
confidence: 99%